Quantificação de ácidos graxos de alevinos de tilápia do Nilo (Oreochromis niloticus) alimentados com diferentes fontes de óleos vegetais - Higuchi, Leticia Hayashi; Feiden, Aldi; Matsushita, Makoto; Santarosa, Mayara; Zanqui, Ana Beatriz; Bittencourt, Fábio [UNESP]; Boscolo, Wilson Rogério (Universidade Estadual de Londrina, 2013)
The present work aimed to quantify the fatty acids in total lipids of Nile tilapia fingerlings (Oreochromis niloticus) fed with different sources of vegetable oils mechanically extracted. Were used 320 tilapias (O. niloticus) with average initial weight and average total initial length of 2.55±0.57 g and 5.59±0.43 cm, respectively, fed for a period of 60 days, in a randomized block design with eight treatments and four replications. The diets were prepared with 320 g/kg crude protein and 3.500 kcal of digestible energy per kg of feed enriched with eight different oils: sunflower, canola, sesame, linseed, peanut, Para's nut soy and macadamia, with an addition of 4%. Among the major fatty acids the oleic, palmitic, linolenic and linoleic were obtained in higher concentration (mg/g of LT) in fish from all treatments. The sums of polyunsaturated fatty acids after 60 days of cultivation had increased in all treatments compared to the 30 days of the experiment. This is due to the addition of oils with high contents of n-6 and n-3 fatty acids. The fatty acids in the carcass are a reflection of the energy source of oil used. As a conclusion it is recommended the use of linseed oil in the diet of tilapia fingerlings due to great improvement in the relationship between n-6/n-3.
Quantification of fatty acids in tilapia fingerlings (Oreochromis niloticus) fed with different sources of vegetable oils
Keywords: Incorporation; Linseed; Lipid source; Requirement